Impact of Psychiatric Comorbidity on Health Care Use in Rheumatoid Arthritis: A Population‐Based Study. Issue 1 (30th December 2020) - Hitchon, Carol A.; Walld, Randy; Peschken, Christine A.; Bernstein, Charles N.; Bolton, James M.; El‐Gabalawy, Renée; Fisk, John D.; Katz, Alan; Lix, Lisa M.; Marriott, James; Patten, Scott B.; Sareen, Jitender; et al.
Abstract : Objective: Psychiatric comorbidity is frequent in rheumatoid arthritis (RA) and complicates treatment. The present study was undertaken to describe the impact of psychiatric comorbidity on health care use (utilization) in RA. Methods: We accessed administrative health data (1984–2016) and identified a prevalent cohort with diagnosed RA. Cases of RA (n = 12, 984) were matched for age, sex, and region of residence with 5 controls (CNT) per case (n = 64, 510). Within each cohort, we identified psychiatric morbidities (depression, anxiety, bipolar disorder, and schizophrenia [PSYC]), with active PSYC defined as ≥2 visits per year. For the years 2006–2016, annual rates of ambulatory care visits (mean ± SD per person) categorized by provider (family physician [FP], rheumatologist, psychiatrist, other specialist), hospitalization (% of cohort), days of hospitalization (mean ± SD), and dispensed drug types (mean ± SD per person) were compared among 4 groups (CNT, CNT plus PSYC, RA, and RA plus PSYC) using generalized linear models adjusted for age, sex, rural versus urban residence, income quintile, and total comorbidities. Estimated rates are reported with 95% confidence intervals (95% CIs). We tested within‐person and RA‐PSYC interaction effects. Results: Subjects with RA were mainly female (72%) and urban residents (59%), with a mean ± SD age of 54 ± 16 years. Compared to RA without PSYC, RA with PSYC had more than additive (synergistic) visits (standardized mean difference [SMD] 10.92 [95% CI 10.25, 11.58]), hospitalizations (SMD 13% [95% CI 0.11, 0.14]), and hospital days (SMD 3.63 [95% CI 3.06, 4.19]) and were dispensed 6.85 more medication types (95% CI 6.43, 7.27). Cases of RA plus PSYC had increased visits to FPs (an additional SMD 8.92 [95% CI 8.35, 9.46] visits). PSYC increased utilization in within‐person models. Conclusion: Managing psychiatric comorbidity effectively may reduce utilization in RA.